Novel Colonoscopic Removal of a Retained Appendix after Surgical Inversion in a Pediatric Case of Malrotation - Sushma Achugatla; Surendra Singh; Sonia Thakur; Rajeev Redkar (Journal of Indian Association of Pediatric Surgeons)
In a child with intestinal malrotation, Ladd’s procedure is performed, and an inversion appendectomy could be a part of this operation. An incidental appendectomy could be a beneficial adjunctive surgery to a laparotomy, and it is true that appendix transection can cause some bacterial infections. Likewise, inversion of the appendix is performed as a part of Ladd’s procedure in the pediatric population to avoid the risk of infection. Inversion of the appendix into itself and into the caecum is a simple, safe procedure in noninflamed conditions. However, there is no such reported case in the pediatric population in the English literature that describes an appendicitis in an operated case of malrotation with Ladd’s procedure and managed by this novel technique.